Numerical Integration over Pyramids (Advances in Applied Mathematics and Mechanics, 2013)
Pyramidal elements are often used to connecttetrahedral and hexahedral elements in the finite element method. In thispaper we derive three new higher order numerical cubature formulae forpyramidal elements.